Hubungan Pemberian ASI Ekslusif dengan Kejadian Stunting Pada Balita di Kelurahan Hadimulyo Timur Kabupaten Kota Metro Provinsi Lampung - Khairani, Adinda Safira; Soviana, Elida (Indonesian Journal of Nutrition Science and Food, 2022)
Background : Stunting is a condition of failure to thrive that occurs in toddlers due to chronic malnutrition. Prevalence stunting in 2019 in Lampung is 26,26%. Prevalence stunting in East Hadimulyo region in 2020 was 13,75%, this figure is above the Metro City average of 12,38%. One of the factors stunting is Exclusive Breastfeeding. The digestive system of toodlers is not perfect at age of 6 months. Objective : The purpose of this study was to analyze the correlation between Exclusive Breastfeeding and Stunting in toddlers in East Hadimulyo Metro City Lampung Province in 2021. Methodology: This study was an observational study with a cross-sectional study design. Data used in this study used secondary data in February 2021 in the form of Exclusive Breastfeeding and Stunting data. Population in this study was toddlers aged 2 to 5 years. The statistical test used fisher-exact. Results : Results of the study on Exclusive Breastfeeding showed that 1 toddler was given exclusive breastfeeding and stunting, 60 toddlers who were not given exclusive breastfeeding had a normal nutritional status and 9 toddlers who were not given exclusive breastfeeding experienced stunting. The results of statistical test using the fisher-exact obtained p-value 0,143 which meant that there was no correlation between exclusive breastfeeding and incidence of stunting in toddlers. Conclusion :It can be concluded there was no correlation between Exclusive Breastfeeding and Incidence of Stunting in toddlers in East Hadimulyo Metro City Lampung Province in 2021.